Hubungan Pengetahuan, Sikap, dan Dukungan Keluarga dengan Kepatuhan Konsumsi Tablet Tambah Darah pada Ibu Hamil Trimester III - Rahmawati, Lusi; Jasmawati, Jasmawati; Nulhakim, Lukman (POLTEKKES KEMENKES MANADO, 2024)
Background: Anemia gravidarum is a condition of mothers with hemoglobin levels <11 grams (trimester I and III) or levels <10.5 grams (trimester II). The cause of anemia is iron deficiency due to pregnant women's non-compliance in taking blood supplement tablets. Objective : To determine the relationship between knowledge, attitudes and family support with compliance with the consumption of blood supplement tablets in pregnant women in the third trimester in the Muara Kaman Community Health Center Working Area. Method : Approach Cross Sectional, The sample studied was 44 people using techniques Purposive Sampling. The independent variables are knowledge, attitudes, and family support. The dependent variable is compliance with consuming blood supplement tablets. The statistical test used is Test Chi Square. Results : Statistical test results The significance value obtained for knowledge was 0.013 (p<α), attitude was 0.001 (p<α), and family support was 0.000 (p<α). in third trimester pregnant women. As a recommendation, the role of health workers is needed in providing health education and empowering families in monitoring the consumption of blood supplement tablets in pregnant women.